Evaluate the limit
x → ∞ lim e x 2 + 1 − e x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Preliminary results: x → ∞ lim x 2 + 1 − x = 0 x → ∞ lim 2 x 2 x 2 + 1 + x x 2 + 1 = 1 These can be proven with basic algebraic manipulations. Keep those in mind when following the computation:
x → ∞ lim e x 2 − 1 − e x = x → ∞ lim e x ( e x 2 + 1 − x − 1 ) = x → ∞ lim e − x e x 2 + 1 − x − 1 = We may now use L'hopital's rule: x → ∞ lim − e − x e x 2 + 1 − x ( x 2 + 1 x − 1 ) = x → ∞ lim e x 2 + 1 ( 1 − x 2 + 1 x ) =
A little algebra before we continue: 1 − x 2 + 1 x = x 2 + 1 x 2 + 1 − x = x 2 + 1 ( x 2 + 1 + x ) 1 = x 2 + 1 + x x 2 + 1 1 . So the previous limit equals:
x → ∞ lim x 2 + 1 + x x 2 + 1 e x 2 + 1 = x → ∞ lim 2 x 2 e x = ∞
Problem Loading...
Note Loading...
Set Loading...
Take the function f ( x ) = e x
At [ x 2 , x 2 + 1 ] by mean value theorem we know that ∃ ξ ∈ [ x 2 , x 2 + 1 ] that f ′ ( ξ ) = x 2 + 1 − x 2 f ( x 2 + 1 ) − f ( x 2 ) or f ′ ( ξ ) = e x 2 + 1 − e x We have : x → ∞ ⇒ x 2 → ∞ ⇒ ξ → ∞ Plus, we have that f ′ ( ξ ) = 2 ξ e ξ so, we evaluate the limit : ξ → ∞ lim f ′ ( ξ ) and by De'l hospital rule we get : x → ∞ lim e x 2 + 1 − e x = + ∞